45 Gy is not sufficient radiotherapy dose for Group III orbital embryonal rhabdomyosarcoma after less than complete response to 12 weeks of ARST0331 chemotherapy: A report from the Soft Tissue Sarcoma Committee of the Children's Oncology Group. Issue 9 (26th May 2017) - Ermoian, Ralph P.; Breneman, John; Walterhouse, David O.; Chi, Yueh‐Yun; Meza, Jane; Anderson, James; Hawkins, Douglas S.; Hayes‐Jordan, Andrea A.; Parham, David M.; Yock, Torunn I.; Donaldson, Sarah S.; Wolden, Suzanne L.
Abstract: Background: Recent Children's Oncology Group (COG) trials tested the efficacy of reduced therapy in an effort to lessen late effects compared to the Intergroup Rhabdomyosarcoma Study (IRS) IV regimen with associated hematologic and hepatic toxicity, and infertility. Here, we analyze the efficacy of 45 Gray (Gy) local radiotherapy (RT) in patients with Group III orbital embryonal rhabdomyosarcoma (ERMS) enrolled on the COG low‐risk study ARST0331. Procedure: Sixty‐two patients with Group III orbital ERMS were treated on ARST0331 with four cycles of vincristine (VCR), dactinomycin (DACT), and cyclophosphamide (CPM; VAC, total cumulative CPM dose 4.8 g/m 2 ) followed by four cycles of VCR and DACT over 22 weeks. Forty‐five Gray of radiation was administered in 25 fractions beginning at week 13 of therapy. Results: Fifty‐three patients were evaluable for this response analysis; seven had missing week 12 response evaluation data and two had progressive disease prior to starting RT. Median follow‐up was 7.8 years. None of the 15 patients with radiographic complete response (CR) compared to 6 of the 38 patients with <CR after 12 weeks of VAC chemotherapy had local recurrences ( P = 0.11). There was no difference in overall survival by response at week 12 ( P = 0.52). Conclusions: For patients with Group III orbital ERMS achieving a CR following VAC chemotherapy that includes modest dose CPM, 45 Gy may be sufficient for durable failure‐free survival. However, for those with <CR treated with the ARST0331 systemic therapy, a different local therapy approach may be needed to achieve the control rate of IRS‐IV without its toxicity.